Gender beyond male and female: Occurrence of a gynandromorph in the Japanese encephalitis vector Culex sitiens (Diptera: Culicidae) - Low, Van Lun; Wong, Meng Li; Liew, Jonathan Wee Kent; Pramasivan, Sandthya; Jeyaprakasam, Nantha Kumar; Vythilingam, Indra (Elsevier, 2020)
A gynandromorph of Culex sitiens Wiedemann (Diptera: Culicidae) was attracted to a human during a mosquito surveillance programme conducted in Kuala Lipis, Pahang, Malaysia on July 20, 2019. Gynandromorphism was observed in antennae, maxillary palps, legs and wings of the specimen, with distinct male characters on the left and female characters on the right, though the left maxillary palp is slightly shorter than the proboscis of a typical male. The abdomen, however, displays well-developed male genitalia. This study represents the first report of oblique gynandromorphism in Cx. sitiens, one of the vectors of Japanese encephalitis in Asia. © 2019 Elsevier B.V.